GENI as an AMPK Activator Binds α and γ Subunits and Improves the Memory Dysfunction of Alzheimer’s Disease Mouse Models via Autophagy and Neuroprotection - Ying Wang; Lanjie Li; Danni Chen; Jiaheng Shan; Meijuan Yi; Hiroyuki Osada; Minoru Yoshida; Lan Xiang; Jianhua Qi (Antioxidants)
Geniposidic 4-isoamyl ester (GENI) with anti-aging effects is a new iridoid glycoside derivative from Gardenia jasminoides Ellis found in our previous study. In this study, to indicate whether this compound has anti-Alzheimer’s disease (AD) effect, the galactose-induced AD mice and naturally aging mice with AD were used to do drug efficacy evaluation. Furthermore, the Western blot, small interfering RNA (siRNA), drug affinity responsive target stability (DARTS), cellular thermal shift assay (CESTA), liquid chromatography-tandem mass spectrometry (LC/MS-MS), adenosine 5′-monophosphate-activated protein kinase (AMPK) mutants and surface plasmon resonance (SPR) analysis were utilized to clarify the mechanism of action and identify target protein of this molecule. GENI exerts anti-AD efficacy in galactose-induced AD mice and naturally aging mice with AD through neuroprotection and modification of autophagy and neuron inflammation. Moreover, AMPK as the target protein of GENI to produce an anti-AD effect is identified and the ASP148, ASP157, and ASP166 of the AMPK α subunit and lysine (LYS)148, aspartic acid (ASP)156, LYS309, and ASP316 in the AMPK γ subunit as binding sites are confirmed. Meanwhile, the AMPK/unc-51-like autophagy-activating kinase 1 (ULK1)/microtubule-associated protein 1 light chain 3 beta (LC3B) and AMPK/mammalian target of rapamycin (mTOR) signaling pathways involved in anti-AD effects of GENI. The findings provide a new perspective on treating neurodegenerative diseases by activating AMPK for the energy metabolism disorder.